Foreign Competition and Disintermediation: No Threat to the German Banking System? - Stefan M. Golder; Claudia M. Buch (Kiel Institute of World Economics (IfW), 1999)
The German financial system is characterized by lower degrees of penetration by foreign commercial banks and of (bank) disintermedation than, for instance, that of the United States. These differences between the two countries could be attributed to the fact that universal banking in Germany creates implicit barriers to entry. Yet, regulatory and informational differences which are unrelated to universal banking could be responsible for the observed difference as well. This paper provides a stylized theoretical model of the banking industry, which suggests that market segmentation and limited market entry can be due to a number of factors, including information costs. Preliminary empirical evidence does not provide clear evidence for the hypothesis that universal banking is the reason for the observed differences in financial systems.
Keywords: G14; G21; 330; Competition in banking; universal banking; information costs; Germany; United States; Bankensystem; Internationale Bank; Finanzintermediaer; Securitization; Internationaler Wettbewerb; Markteintritt; Universalbank; Informationskosten; Vergleich; Deutschland; Vereinigte Staaten